Початки наукового зацікавлення українським фольклором (збирання і вивчення) - Кирчів, Р. (Народна творчість та етнографія, 2006)
The following article is the continuation of the research published in № 1/2006. The article speaks on the formation of Ukrainian folklore studies. The author mentions the first steps made in the researches of the 18th-19th centuries. The author researches several scholars of that time and their collections of folklore. A part of the article is dedicated to folklore activities of Z. Dolenga-Khodakovskyj. The arousal of folklore studies and their peculiarities in Galychyna are depicted in details, particularly the work of Ludwig Pjontkevych.